Loaded pistols - English, John, 1903-1969; Cummins, Dwight; Yost, Dorothy; Autry, Gene, 1907-1998; Britton, Barbara, 1919-1980; Columbia Pictures Corporation; Gene Autry Productions; Cinetel Films ([Los Angeles, CA] : Gene Autry Productions, 1948)
Following the death of his friend Ed Norton who was killed during a dice game, Gene Autry sets out in search of the killer. His search takes him to an old house where Larry Evans, who was accused of the murder, is in hiding. Larry's sister Mary defends her brother, claiming they both loved Ed, who acted as their guardian after the death of their father. Mary is able to convince Gene that Larry is innocent. Gene offers to help him evade the sheriff until he can discover the real killer. --
Originally released as a motion picture in 1948.
Gene Autry, Barbara Britton, Chill Wills, Jack Holt, Russell ARms, Robert Shayne, and Champion.
Cinematographer, William Bradford; editor, Aaron Stell; music, Arthur Morton.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 8, 2016).
Keywords: Murder -- Drama; Musical films; Feature films; Internet videos; Streaming video